THE USING OF STORYTELLING IN TEACHING VOCABULARY TO IMPROVE ENGLISH LITERACY OF THE FIFTH GRADERS AT SDIT SAMAWI YOGYAKARTA - Rahayu Rahayu; Khoirotul Ummayah (Universitas Muhammadiyah Purwokerto, 2023)
This research is aimed to find out the effect of using storytelling in teaching vocabulary to improve English literacy of the fifth graders at SD IT Samawi Yogyakarta. This research method was Quasi Experimental Research, while the research design used Nonequivalent Control Group Design. The sample in this research was students of class 5. Class 5 Ar Rozi (24 students) as the experimental class and class 5 Ibnu Rusyd (26 students) as the control class. The experimental group was students taught using storytelling whereas the control group was students taught using conventional technique. The data were obtained by using pre-test and post-test. The pre-test was given to both groups before the treatment and the post-test was given after the treatment. The data of the pre-test and post-test of both groups were analyzed by using descriptive and inferential statistics. After the data were tested and found to be homogeneous and normal, the hypothesis was tested using t-test. In the experimental group the average of post-test was 76.6 and the control group was 70.4. The result of hypothesis t-test showed that the significance value was 0,026 < 0,05. It means that there was significant difference in learning achievement between students who taught by using storytelling and those taugh by using conventional technique.